Color Image Compression Scheme with Reduced Computational Complexity - Sabriya Alfitouri; Najat Ali; Braika Alameen; Ali Ahmed, Abdussalam (AlQalam Journal of Medical and Applied Sciences, 2022)
Block Truncation Coding "BTC" is a simple and fast algorithm for coding digital images, which achieves constant bit rate of 2 bits per pixel. The compression may be improved by coding only a half of the bits in the BTC bit plane of each block; the other half will be interpolated. The resulting bit rate will be 1.5 bits per pixel. A low computational complexity compression scheme for coding color images based on Absolute Moment Block Truncation Coding "AMBTC" is presented in this paper. Four techniques are employed in this compression scheme. They are quad tree segmentation, absolute moment block truncation coding bit plane omission, bit plane coding using 32 predefined visual patterns and one of the interpolative bit plane coding techniques. The algorithm has been investigated and applied to different still color images. The simulation results show that the scheme achieves an average bit rate of 0.385 bits per pixel for color images with an average PSNR of 30.71 dB.